Instructional leadership and instructor development: a case study of Malaysia's research universities - Fahimirad, Mehrnaz; Idris, Khairuddin; Kotamjani, Sedigheh Shakib (Faculty of Social Sciences and Humanities, National University of Malaysia, 2016)
Universities are affected by internal factors such as when certain self-imposed procedures complicate the delivery of teaching and learning and thus depriving students and lecturers of needed creativity, flexibility, and time to optimize meaningful learning. A lack of systematic succession planning in academic leadership may also detract from maintaining continuity in the teaching and learning of related policies and practices. All these factors contribute to the need to reconceptualize university teaching and learning. This study provided an in-depth look at the practices of instructional leadership in Malaysian research universities. Primary data were gathered from thematic in-depth interviews. The findings revealed that the research universities planned sustained programmes of educational development , adopted principles of effective learning and teaching, and designed conducive learning environments for students. Academics need a supportive culture to put these principles into practice. Finally, creating a learning culture depended not only on well-educated, well-meaning individual academics but also an academic community working together to create a student-centered attitude.